JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Objective This study evaluated the clinical application, outcomes, and prognostic indicators of deep digital flexor tenotomy (DDFT) in horses with chronic laminitis. Methods A computer-generated search identified all possible cases of laminitis for horses referred to the George D. Widener Hospital for Large Animals at the University of Pennsylvania between 2010 and 2022. Medical records were reviewed for a diagnosis of laminitis by clinical examination and radiographs. The population was characterized by breed, age, clinical features, and radiographic findings. Poisson regression was performed to identify variables associated with outcomes after DDFT. Results A total of 871 horses were included in the analyses, of which 8% of the population had undergone DDFT. Multivariable modeling showed that the risk of developing complications with the third phalanx increased by 16%/y of age (incidence rate ratio, 1.16; 95% CI, 1.03 to 1.30). Horses that underwent tenotomy showed a 20-fold improvement postsurgery at 3 to 6 months (incidence rate ratio, 20:1; 95% CI, 1.1 to 380.9). Conclusions Results emphasized the selectivity of surgical candidacy and the ongoing debate over DDFT's role as a salvage procedure, providing insight into animal selection and the need for evidence-based criteria to guide the timing and application of DDFT in chronic laminitis cases. Clinical relevance Notwithstanding inconsistent outcomes reported in the literature, this study provided guidance for DDFT with corrective shoeing in a subset of chronic laminitis cases. It presents a viable option for those cases that fail to respond to medical and farriery management.